Does leverage affect labour productivity? A comparative study of local and multinational companies of the Baltic countries - Avarmaa, Mari; Hazak, Aaro; Männasoo, Kadri (Journal of Business Economics and Management, 2013)
This paper investigates the impact of leverage on labour productivity of companies operating in the Baltic countries, with a focus on differences between local and multinational companies. We employ a fixed effects regression model on company level data, covering the period from 2001 to 2008. Our results demonstrate that the impact of leverage on labour productivity is non-linear and it differs dramatically between local and multinational companies. In the case of local companies, at low levels of leverage, an increase in external financing tends to bring along an improvement in labour productivity, while at higher levels of leverage an increase in debt financing appears to result in a loss of labour productivity. For multinational companies, the impact of leverage on labour productivity tends to be more linear and leverage appears to have a negative impact on labour productivity. Although debt overhang is believed to be an issue in the Baltic countries in general, local companies with low leverage might be able to increase labour productivity by additional borrowing. First published online: 19 Oct 2012